Simple generation of a dirhodium μ-carbido complex via thiocarbonyl reduction. Issue 29 (3rd July 2018) - Barnett, Harrison J.; Burt, Liam K.; Hill, Anthony F.
Abstract : The reaction of [RhCl(CS)(PPh3 )2 ] with excess catecholborane affords the cumulenic carbido complex [Rh2 (μ-C)Cl2 (PPh3 )4 ] which undergoes phosphine and halide substitution to afford a range of complexes in which the RhCRh spine remains intact. Abstract : The reaction of [RhCl(CS)(PPh3 )2 ] with excess catecholborane affords the cumulenic carbido complex [Rh2 (μ-C)Cl2 (PPh3 )4 ] which undergoes phosphine and halide substitution to afford a range of complexes in which the RhCRh spine remains intact. Amongst these, the reactions with K[L] (L = H2 B(pz)2, H2 B(pzMe2 )2, HB(pz)3 ; pz = pyrazol-1-yl) afford [Rh2 (μ-C)(PPh3 )2 (L)2 ] whilst with K[HB(pzMe2 )3 ] the unsymmetrical complex [Rh2 H(μ-C)(μ-C6 H4 PPh2 -2){HB(pzMe2 )3 }2 ] is obtained in which the carbido ligand spans d 6 -Rh(iii ) and d 8 -Rh(i ) centres.